2005
DOI: 10.1111/j.1582-4934.2005.tb00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of cultured skin substitutes

Abstract: Skin replacement has been a challenging task for surgeons ever since the introduction of skin grafts by Reverdin in 1871. Recently, skin grafting has evolved from the initial autograft and allograft preparations to biosynthetic and tissue-engineered living skin replacements. This has been fostered by the dramatically improved survival rates of major burns where the availability of autologous normal skin for grafting has become one of the limiting factors. The ideal properties of a temporary and a permanent ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
163
0
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(177 citation statements)
references
References 127 publications
(152 reference statements)
0
163
0
14
Order By: Relevance
“…They observed that increased rate of re-epithelisation of partial thickness superficial burn by the use of amniotic membrane 4 . This stimulatory effect of on epithelisation & has been considered to be mediated by growth factors and progenic for cell released by amniotic membrane 9,10,11 . …”
Section: Discussionmentioning
confidence: 99%
“…They observed that increased rate of re-epithelisation of partial thickness superficial burn by the use of amniotic membrane 4 . This stimulatory effect of on epithelisation & has been considered to be mediated by growth factors and progenic for cell released by amniotic membrane 9,10,11 . …”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic epidermal cell grafts have not been implemented as an alternative to cultured autografts in large burns, largely because adult cells-in contrast to fetal ones [13]-are highly immunogenic and are not, therefore, an option for a permanent substitute in large burns [14,15]. In contrast, allogeneic cell therapy products have been successfully developed for temporary replacement that is taking into account the short lifespan of the grafted cells.…”
Section: The Need For Complements and Alternativesmentioning
confidence: 99%
“…When introduced into the body they start degrading and leave behind a matrix of connective tissues having similar properties as that of the dermis. The effects of collagen on dermal wound healing and its combination with anti-microbial agents have been reported 51 . It was observed that it increased the formation of granulation tissue during wound healing.…”
Section: Semi-permeable Adhesive Film Dressingsmentioning
confidence: 99%